Answer:
Simplifying
15 + 12x + -5x + 4y + -7 = 0
Reorder the terms:
15 + -7 + 12x + -5x + 4y = 0
Combine like terms: 15 + -7 = 8
8 + 12x + -5x + 4y = 0
Combine like terms: 12x + -5x = 7x
8 + 7x + 4y = 0
Solving
8 + 7x + 4y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8' to each side of the equation.
8 + 7x + -8 + 4y = 0 + -8
Reorder the terms:
8 + -8 + 7x + 4y = 0 + -8
Combine like terms: 8 + -8 = 0
0 + 7x + 4y = 0 + -8
7x + 4y = 0 + -8
Combine like terms: 0 + -8 = -8
7x + 4y = -8
Add '-4y' to each side of the equation.
7x + 4y + -4y = -8 + -4y
Combine like terms: 4y + -4y = 0
7x + 0 = -8 + -4y
7x = -8 + -4y
Divide each side by '7'.
x = -1.142857143 + -0.5714285714y
Simplifying
x = -1.142857143 + -0.5714285714y
Step-by-step explanation: